Animal Models of CNS Viral Disease: Examples from Borna Disease Virus Models - Solbrig, Marylou V. (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Borna disease (BD), caused by the neurotropic RNA virus, Borna Disease virus, is an affliction ranging from asymptomatic to fatal meningoencephalitis across naturally and experimentally infected warmblooded (mammalian and bird) species. More than 100 years after the first clinical descriptions of Borna disease in horses and studies beginning in the 1980's linking Borna disease virus to human neuropsychiatric diseases, experimentally infected rodents have been used as models for examining behavioral, neuropharmacological, and neurochemical responses to viral challenge at different stages of life. These studies have contributed to understanding the role of CNS viral injury in vulnerability to behavioral, developmental, epileptic, and neurodegenerative diseases and aided evaluation of the proposed and still controversial links to human disease.